A model for Chinese transnational migration through the Americas: the Canadian experience. Issue 2 (2014) - Sheau‐yueh Janey Chao
<x xml:space="preserve"> Abstract </x> Purpose – This article was based on the information from The 5th International Conference of Institutes and Libraries for Chinese Overseas Studies held in the University of British Columbia in Vancouver, BC, Canada in which the author was a presenter in session 4.2.9a of the Early life of Yuan Shikai and the formation of Yuan family. The paper aims to include comprehensive analysis and development of the history of Chinese migration. An annotated bibliography of suggested readings was offered to highlight the subject knowledge for further research in this area. Design/methodology/approach – The paper includes comprehensive analysis and development of the history of Chinese migration and the experiences and family histories of overseas Chinese in Canada. An annotated bibliography of suggested readings was offered to highlight the subject knowledge for further research in this area. Findings – The paper offers full description and comprehensive analysis of the history of Chinese migration and overseas Chinese studies in Canada. A bbibliography of suggested readings was offered for further research in this area. Research limitations/implications – This research study has a strong subject focus on Chinese migration, overseas Chinese studies, and resource‐sharing in the subject area. It is a specific field for research in Asian studies. Practical implications – The result of this study will assist students, researchers, and the general public in the area of overseas Chinese studies and developing their interests in the social and historical value of Chinese migration history and resource‐sharing in the area. Originality/value – Very little research has been done in the area of Chinese migration and historical development. The paper would offer historians, sociologists, ethnologists, librarians, administrations, professors, as well as students in the fields of Asian history, anthropology, sociology, political science, geography, and other Asian‐related interdisciplinary studies.